2018
DOI: 10.1021/acs.est.7b05707
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Photopromoted Release of Vanadium from Vanadium Titano-Magnetite

Abstract: The release of V from vanadium titano-magnetite, a predominant natural source of V, was studied under light irradiation. The release rate of V from vanadium titano-magnetite was accelerated by light irradiation, and the oxidation of V was detected. The essence of the photopromoted release of V is that the immobile low valence V is transformed to the mobile V(V) by photoinduced active species generated from the photocatalysis process of magnetite. Among the photoinduced active species, •OH and HO were recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…As2S3 + •O2¯ + H + → 3S•¯(s) + HO2¯ + 2As(III) fast (14) As2S3 + 3•OH + 3H + → 3S•¯(s) + 3H2O + 2As(III) k = 9×10 9 M -1 s -1 (15) During the photo-reaction process, As(III) can be released. The specific species of the released As(III) is highly dependent on the pH values and S 2concentration.…”
Section: The Effects Of •O2¯ and •Oh On Arsenic Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…As2S3 + •O2¯ + H + → 3S•¯(s) + HO2¯ + 2As(III) fast (14) As2S3 + 3•OH + 3H + → 3S•¯(s) + 3H2O + 2As(III) k = 9×10 9 M -1 s -1 (15) During the photo-reaction process, As(III) can be released. The specific species of the released As(III) is highly dependent on the pH values and S 2concentration.…”
Section: The Effects Of •O2¯ and •Oh On Arsenic Oxidationmentioning
confidence: 99%
“…Recently, the effect of light on the dissolution of minerals containing heavy metals has been studied to elucidate the mechanism of photocorrosion reactions on the release of metal ions, such as antimony and vanadium, from their parental minerals or the synthesized substitutes (e.g. senarmontite (Sb2O3) [13], stibnite (Sb2S3) [14], and vanadium titano-magnetite [15]. It has been demonstrated that simulated sunlight or UV irradiation can promote the dissolution of minerals and thus release heavy metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Natural iron minerals are a group of inorganic compounds widespread in water, atmosphere, and soil. Recent studies have revealed the semiconducting properties of iron minerals, where sunlight irradiation triggers the generation and separation of charge carriers (i.e., electrons and holes). Those photogenerated charge carriers could migrate to the iron mineral surface, producing photocurrents and mediating numerous biogeochemical reactions. For instance, photooxidation of organic compounds and arsenite was observed on the surface of hematite and goethite. In addition, microbes can utilize the photogenerated electrons from hematite for Cr­(VI) reduction .…”
Section: Introductionmentioning
confidence: 99%
“…28 The transformation of less mobile V(III) and V(IV) to mobile V(V) by photoinduced active species (•OH and H 2 O 2 ) produced by the photocatalysis of vanadium titano-magnetite under light irradiation, which supplements the geochemical V processes, has been revealed in laboratory studies. 115 Protonpromoted dissolution of V(III), V(IV), and V(V) oxides at pH 3.1−10.0 has also been studied, and these processes follow a surface-controlled reaction mechanism accompanied by redox reactions under environmental conditions. 116 Natural oxidizing minerals, such as birnessite, can oxidize V(IV) into highly mobile and toxic V(V) under neutral pH conditions.…”
Section: T H Imentioning
confidence: 99%
“…V­(III) and V­(IV) precipitates in minerals tend to be oxidized to soluble V­(V) in the presence of oxygen, causing V mobilization . The transformation of less mobile V­(III) and V­(IV) to mobile V­(V) by photoinduced active species (•OH and H 2 O 2 ) produced by the photocatalysis of vanadium titano-magnetite under light irradiation, which supplements the geochemical V processes, has been revealed in laboratory studies . Proton-promoted dissolution of V­(III), V­(IV), and V­(V) oxides at pH 3.1–10.0 has also been studied, and these processes follow a surface-controlled reaction mechanism accompanied by redox reactions under environmental conditions .…”
Section: Migration and Transformationmentioning
confidence: 99%